Laser microfabrication : thin film processes and lithography - Ehrlich, Daniel J.; Tsao, Jeffrey Y. (Academic Press, 1989)
This book reviews the solid core of fundamental scientific knowledge on laser-stimulated surface chemistry that has accumulated over the past few years. It provides a useful overview for the student and interested non-expert as well as essential reference data (photodissociation cross sections, thermochemical constants, etc.) for the active researcher.